Pendampingan Implementasi Perangkat Pembelajaran Berbasis Etno-STEM Bagi Guru IPA di SMP/ MTs Muhammadiyah Sidoarjo - Budi Sartika, Septi; Efendi, Nur; Liansari, Vevy (Universitas Muhammadiyah Sidoarjo, 2022)
Local wisdom becomes something that is important enough to be introduced and applied by students. The development of technology until anytime will continue to occur because basically humans need technology to ease the burden of life. This has been embodied in one of the learning based ethno-STEM strategies. This learning strategy has been able to introduce and train students with local wisdom. Methods of mentoring activities include planning, implementation, and evaluation. In the planning stage, equalization of perceptions of the use of learning based ethno-STEM devices and instruments for Class VII, VIII, and IX Even Semesters has been developed and has been registered with Intellectual Property Rights. At the implementation stage, it needs to be reviewed by disseminating the implementation of learning based ethno-STEM devices and instruments to more schools. With this dissemination activity, it is expected that there will be input for the improvement of learning based ethno-STEM devices and instruments so that it will be better. At the evaluation stage, the dissemination results there are 8 schools have been accompanied in implementing of learning based ethno-STEM devices noted the obstacles faced. The obstacles faced in the implementation of learning based ethno-STEM devices and instruments include the difficulty level of natural science material each chapter is different, teacher-centered classroom management, the existence of facilities and infrastructure that do not support the learning process, and student activities that are not relevant to learning. These constraints are further sought solutions and used as a basis for revising learning based ethno-STEM devices and instruments for natural science subjects so that they are obtained devices and instruments that are much better than before.